2019
DOI: 10.1038/s41409-019-0676-0
|View full text |Cite
|
Sign up to set email alerts
|

Results from a multicenter, noninterventional registry study for multiple myeloma patients who received stem cell mobilization regimens with and without plerixafor

Abstract: Plerixafor plus granulocyte-colony stimulating factor (G-CSF) enhances the mobilization of hematopoietic stem cells (HSCs) for collection and subsequent autologous hematopoietic stem cell transplantation (HSCT) in patients with multiple myeloma (MM). This international, multicenter, noninterventional registry study (NCT01362972), evaluated long-term outcomes for MM patients who received plerixafor versus other mobilization regimens. The comparisons were: G-CSF + plerixafor (G-CSF + P) versus G-CSF-; G-CSF + P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…The impact of Plerixafor on transplant outcomes is difficult to evaluate, due to the confounding factor that those receiving Plerixafor are largely poor mobilizers and therefore more likely to have poorer OS and PFS [17]. In studies selecting for predicted or proven poor mobilizers, Plerixafor use has been shown not to affect transplant outcomes [17, 18] suggesting there is not an advantage to using G‐CSF + Plerixafor over Cyclo‐G. Conversely, mobilization using cyclophosphamide incurs risk associated with the use of alkylating agents; namely febrile neutropenia and increased episodes of hospitalisation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of Plerixafor on transplant outcomes is difficult to evaluate, due to the confounding factor that those receiving Plerixafor are largely poor mobilizers and therefore more likely to have poorer OS and PFS [17]. In studies selecting for predicted or proven poor mobilizers, Plerixafor use has been shown not to affect transplant outcomes [17, 18] suggesting there is not an advantage to using G‐CSF + Plerixafor over Cyclo‐G. Conversely, mobilization using cyclophosphamide incurs risk associated with the use of alkylating agents; namely febrile neutropenia and increased episodes of hospitalisation.…”
Section: Discussionmentioning
confidence: 99%
“…The negligible impact of Cyclo‐G versus G‐CSF mobilization on subsequent neutrophil engraftment has been previously reported in the literature [16]. The impact of Plerixafor on transplant outcomes is difficult to evaluate, due to the confounding factor that those receiving Plerixafor are largely poor mobilizers and therefore more likely to have poorer OS and PFS [17]. In studies selecting for predicted or proven poor mobilizers, Plerixafor use has been shown not to affect transplant outcomes [17, 18] suggesting there is not an advantage to using G‐CSF + Plerixafor over Cyclo‐G.…”
Section: Discussionmentioning
confidence: 99%
“…We included all consecutive patients with MM from the CALM study who underwent ≥1 ASCT in this cohort between 2008 and 2012. The primary outcomes of the study were previously published [ 1 , 2 ]. Here, we report the analysis of the data collected in the CALM study.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the possibility of tumor cell contamination of plerixaformobilized HPCs cannot be completely ruled out 6,7 . In fact, Morris et al reported that the cumulative incidence of relapse after transplantation was higher in the plerixafor cohort than in the other regimen cohorts 8 .…”
Section: Introductionmentioning
confidence: 96%